Self protective health care in childhood cancer survivors from the perspective of survivors, parents, and professionals: a qualitative study - Masumeh Akbarbegloo; Mahnaz Sanaeefar; Mehrdad Karimi; Marzieh Hoseini (BMC, 2024)
Abstract Introduction Childhood cancer survivors experience many health problems that they must protect themselves from their destructive physical and psychological effects. Understanding experiences of children about self-protective care will help health care providers manage long-term care plans. Therefore, this study was conducted with the aim of exploring self-protection care in childhood cancer survivors. Methods This is a phenomenological study that was conducted in the clinics and cancer care centers of Urmia and Khoy in Iran. 27 participants were selected by purposive sampling until data saturation. The data was collected using a semi-structured and in-depth face to face interview. Content analysis approach used for data analysis and MAXQUDA 10 software used for data management. Results Data analysis led to the emergence of "self-protection health care" as a main category, two categories "maintaining physical health" and "keeping a strong mindset" and 9 sub-categories including "abstain activities that may cause harm", "refusing contact with others for possible infection", "monitoring symptoms and side-effects of cancer coming back", "avoiding unhealthy diet", "knowing about cancer from similar others", "keep away negative thoughts and emotions", "drawing on spiritual resources", "creating a bridge to life again" and "being healthy for the sake of one's family". Conclusion According to the results of this study, self-protection is one of the most important cares for childhood cancer survivors. Over time, the influence of the clinical team and parents on children's health care diminishes. Therefore, they should promote their health and well-being behaviors and use a variety of protective approaches to self-care.